Gastrointestinal tract involvement in granulomatosis with polyangiitis - Masiak, Anna; Zdrojewski, Łukasz; Zdrojewski, Zbigniew; Bułło-Piontecka, Barbara; Rutkowski, Bolesław (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction: Granulomatosis with polyangiitis (GPA) is a necrotising vasculitis of small arteries and veins. In its classical manifestation GPA affects the upper and lower respiratory tract and kidneys. However, other organs, including those of the gastrointestinal tract, may be affected as well. Aim: To present the clinical manifestations of gastrointestinal tract involvement in patients with GPA. Material and methods: We analysed case records of 34 patients with GPA treated in the Department of Nephrology, Transplantology, and Internal Medicine of the Medical University of Gdansk from 1991 to 2009. Results : In 9 of 34 patients, 2 men and 7 women, aged 18 to 74 years, gastrointestinal complications were observed in the course of GPA. In two of them a localised and in seven a generalised type of GPA was diagnosed. The main symptoms relating to gastrointestinal tract were: oral mucosa ulcerations, gum mucosa hypertrophy, dyspepsia, vomiting, stomachache, gastrointestinal haemorrhage, diarrhoea, and symptoms of gastrointestinal tract perforation. Two patients required urgent surgical treatment. In 2 of the 5 patients who developed gastrointestinal bleeding, it was the direct cause of death. The histopathological confirmation of specificity of changes in gastrointestinal tract was established only in 2 cases. Tissue samples collected during endoscopy usually revealed only nonspecific inflammation or the presence of ulcers. Conclusions : Therapeutic strategies accepted for GPA treatment are effective in treating patients with gastrointestinal involvement in the course of the disease. Some complications require surgical intervention.